Resveratrol Improves Liver Steatosis and Insulin Resistance in Non-alcoholic Fatty Liver Disease in Association With the Gut Microbiota - Du, Fan; Huang, Rongfeng; Lin, Dan; Wang, Yuying; Yang, Xiaohuang; Huang, Xiaoyun; Zheng, Biyun; Chen, Zhixin; Huang, Yuehong; Wang, Xiaozhong; Chen, Fenglin (Frontiers in Microbiology, 2021)
Resveratrol (RSV) is a potential alternative therapy for non-alcoholic fatty liver disease (NAFLD) that has been evaluated in many clinical trials, but the mechanisms of RSV action have not been fully elucidated. Recent studies suggested that the gut microbiota is an important RSV target; therefore, we speculated that the gut microbiota might mediate the beneficial effects of RSV in NAFLD. To verify this hypothesis, we established a high-fat diet (HFD)-induced NAFLD mouse model, which was subjected to RSV gavage to evaluate the therapeutic effects. We observed that RSV reduced liver steatosis and insulin resistance in NAFLD. RSV significantly changed the diversity and composition of the gut microbiota according to 16S rRNA sequencing. Gut microbiota gene function prediction showed that the enrichment of pathways related to lipid and glucose metabolism decreased after RSV treatment. Furthermore, correlation analysis indicated that the improvements in NAFLD metabolic indicators were closely related to the altered gut microbiota. We further fermented RSV with the gut microbiota in vitro to verify that RSV directly affected the gut microbiota. Our data suggested that the gut microbiota might be an important target through which RSV exerts its anti-NAFLD effect.